Increasing of Mining Performance by Improving Maintenance Skills - Sakulnamrat, Suthut; Susilo, Leo J (The Indonesian Journal of Business Administration, 2015)
Abstract – PT Tambang Raya Usaha Tama (PT TRUST), established in January 2014, a subsidiary of PT Indo Tambangraya Megah (ITM),It is an integrated mining service company, The concept is to be the best contractor for mining service which can be competitive in mining cost and coal mining business.Based on the historical data year 2014 of PT TRUST, the result of performance indicators was fluctuated and some of the indicators were below the target. The result showed a part of maintenance work which was done as a reaction to unexpected events. Furthermore, it will impact to life cycle cost of equipment which was planned by project feasibility and medium term plan. To increase the capability of Maintenance department through maintenance improvement framework establishment by collecting both of theory and best practices, also the foundation of learning organization.The project methodology aims to help understanding the current state of Maintenance department and related functions. The conceptual introduction of each element is explained and data collection was done mainly using self-assessment questionnaire covering the entire 33 building blocks of maintenance improvement activities answered by the representative staffs based on their individual understanding the current situation at work.The solution is knowledge development by delivering conceptual training to all group leaders to improve the gap of knowledge and competency. The 33 building blocks have interrelation and interdependence in the form of process flow pattern; the description and purposes of installation are presented in conjunction with the application can be applied to Maintenance activities. The training program will be delivered to address the impact of various operational performances and targets as the company has identified.Finally, this project can enhance human skill and improve the competency gap of all group leaders so they can transfer the knowledge to their subordinates. It can develop overall performance efficiency in operation and as a benchmark of company competitiveness in profit value and lower operating cost. Keywords: Overall Equipment Effectiveness (OEE), life cycle cost, maintenance improvement activities, knowledge development